Avaliação de professores sobre o repertório social e acadêmico de alunos com deficiência mental incluídos no ensino regular. - Rosin-Pinola, Andréa Regina (2006)
The school inclusion of pupils with specials educational needs at the regular teaching have been the proposal guide and dominant especial education at the Brazil on last years. With this proposal beginning studies and programs of intervention, that to have in view to evaluate and get better the conditions to your implementation. Studies suggest that with mental deficiency has presented to big difficulties of inclusion. On the attempt to avalue such difficulties and how the deficits in social skills constitute one of the criterion of diagnostic of mental deficiency, its more important identifies to get promote your superation. This study has like purpose: (1) identify the social repertory (socials skills and problems of behavior) and academic skills of children with mental deficiency include, compare with the children of low and high academic performance and normative sample; (2) identify social skills important for school; (3) identify the resources and deficits of social skills with the pupils with mental deficiency include compare with others childrens; (4) check possible relation between social skills, behavior problems, academic performance and intelligence and (5) analyze possible effects of social demographics variables on the social skills and behavior problems the children with mental retardation. To share of this study 30 teachers of children with mental deficiency including in regular schools (publics and privates) of a city in side in state of São Paulo. The teachers evaluating that and others pupils that, conform your indications to get two groups, low academic performance and high academic performance. The teachers evaluating the pupils using the Social Skills Rating Systems (Gresham & Elliott, 1990). The childrens they were also availed by means o Raven-Color Matrix. He answers was computed and analyses with statistic descriptive still evaluating the differences between groups (ANOVA and Test T-Student). The dates indicate that the groups the lower performance and mental deficiency difference the groups de higher performance and normative sample in all factors of social skills, behavior problems and academic performance e difference between it self only in the factors of assertion and self defense. Was check effects the social economic level and the intelligence in variables dependents.